The public sector in the crisis - Glassner, Vera (Brussels, 2010)
"Against the background of governments’ consolidation strategies, ETUI researcher Vera Glassner provides an overview of recent developments in terms of pay, employment and reforms of the pay system in the public sector. Cuts and freezes of public sector wages were most frequently imposed unilaterally by the state. The author argues that the re-establishment of collective bargaining as a mechanism to settle public sector pay is of vital importance in order to prevent downward pressures on wages, maintain workers’ purchasing power and contribute to a stable and balanced economic development within the Eurozone and across the business cycle"